RESIDENT’S PERCEPTION ON LIVABILITY IN AFFORDABLE HOUSING IN MALAYSIA - Raji, Fauziah; Ba Qutayan, Shadiya Mohamed Saleh; Ariffin, Aini Suzana; Razali, Muhammad Najib; Kamarudin, Norhaya (Journal of Technology Management and Business, 2016)
Housing affordability has always been an issue worldwide. With the increase in human population and spiraling house price, governments have been scrambling to build sufficient affordability house to meet the forever increasing demand. In light of this there is concern on the livability aspect of these affordability houses built have been compromised. This research identifies the livability attributes and studies the perception of residents’ in affordable housing towards these attributes. Findings revealed that there is compromise in location of the affordable housing schemes. The findings also signified that the most important issues to the residents were safety and accessibility to health facilities. Interestingly this research suggest that many residents within the affordable housing schemes tend to make do with the situation and would seriously consider moving to better dwellings if the opportunity arises. Keywords: affordability; livability; housing; perception